Economic Potential Management of Grouper Resources in Kolaka Regency, Southeast Sulawesi, Indonesia (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2025)
Grouper is one of the fishery resources that has high economic value. The high price has led to increased exploitation of the grouper out of 163 grouper species worldwide. According to the IUCN, 12% (20 species) are classified as endangered, while 13% (22 species) are categorized as near threatened under the IUCN Red List criteria. This study aims to see the extent of the economic potential of grouper in Kolaka Regency and identify its distribution area. Analysis was done descriptively based on the results of field observations. The results of this research show that the potential of grouper fisheries in Kolaka Regency is quite large. However, the catch per unit of effort (CPUE) of grouper fluctuates every year. A significant increase occurred in 2014, then decreased in 2016, and increased again the following year; in 2017, there was a decrease in 2019, and increased again in 2020 and 2021. This research concludes that grouper fishing occurs more in the waters of Kolaka Regency due to the high fishing activities carried out by local fishermen. Based on these data, management efforts must be carried out immediately to maintain the stock of grouper resources in Kolaka Regency.